New data on Gnaphosidae (Arachnida, Araneae) of Iraq - Zamani Alireza; Ali Al-Yacoub Ghassan A.; Abdullah Najim Shurooq (Pensoft Publishers, 2022)
New faunistic data are provided on the ground spiders (Araneae: Gnaphosidae) of Iraq. Three genera (Haplodrassus Chamberlin, 1922; Minosiella Dalmas, 1921; Odontodrassus Jézéquel, 1965) and six species (Haplodrassus dalmatensis (L. Koch, 1866); Minosiella intermedia Denis, 1958; Odontodrassus aravaensis Levy, 1999; Odontodrassus mundulus (O. Pickard-Cambridge, 1872); Pterotricha dalmasi Fage, 1929; Zelotes fagei Denis, 1955) are reported in Iraq for the first time, and the previously unknown female of Pterotricha kovblyuki Zamani & Marusik, 2018 is described. In addition, a list of all gnaphosids reported from Iraq (16 spp.) is provided.